Financial Analysis in Banking: The Challenge of Segment Reporting*. (5th August 2021) - Bui, Long T.; Magnan, Michel; Moldovan, Rucsandra
ABSTRACT: An equity analyst at Q&M Independent Research Corporation is assessing the financial and business prospects of two Canadian banks: Bank of Montréal and Canadian Imperial Bank of Commerce. Relying on recent information provided in the financial statements and proxy circulars from both banks, the analyst faces some challenges in performing a prospective analysis, a key input to any valuation model. The case highlights the cost‐benefit analysis of disclosure that banks may perform when applying IFRS 8 – Operating Segments. The case also illustrates the challenges that segment disclosure poses to financial analysts and investors as they attempt to forecast a bank's earnings and to perform a valuation. Furthermore, the case develops the process by which a bank's business model is linked with its financial reporting and, ultimately, its valuation. RÉSUMÉ: L'analyse financière dans le secteur bancaire : la difficulté que pose la publication d'informations sectorielles Un analyste boursier chez Q&M Independent Research Corporation évalue les perspectives commerciales et financières de deux banques canadiennes : la Banque de Montréal (BMO) et la Banque Canadienne Impériale de Commerce (CIBC). S'appuyant sur l'information récente fournie dans les états financiers et les circulaires de procuration, l'analyste éprouve des difficultés à réaliser une analyse prospective, qui est un élément clé de tout modèle d'évaluation. Ce cas met en lumière l'analyse coûts‐avantages de la communication d'informations que peuvent effectuer les banques en application de la norme IFRS 8 – Secteurs opérationnels. Il illustre également les difficultés que pose la publication d'informations sectorielles aux analystes financiers et aux investisseurs au moment de prédire les résultats d'une banque et d'effectuer une évaluation. Qui plus est, ce cas présente le processus par lequel le modèle d'affaires d'une banque est lié à ses rapports financiers et, en bout de compte, à son évaluation.